A novel role for the immunophilin FKBP52 in motor coordination - Young, Matthew J.; Geiszler, Philippine C.; Pardon, Marie-Christine (Elsevier, 2016)
FKBP52 is a ubiquitously distributed immunophilin that has been associated with wideranging functions in cell signalling as well as hormonal and stress responses. Amongst other pathways, it acts via complex-formation with corticosteroid receptors and has consequently been associated with stress- and age-related neurodegenerative disorders including Alzheimer’s and Parkinson’s diseases. Reduced levels of FKBP52 have been linked to tau dysfunction and amyloid beta toxicity in AD. However, FKBP52’s role in cognition and neurodegenerative disorder-like phenotypes remained to be elucidated. The present study aimed therefore at investigating the cognitive and behavioural effects of reduced FKBP52 levels of genetically modified mice during ageing. Female and male FKBP52+/+, FKBP52+/- and FKBP52-/- mice were compared at two-, ten-, twelve-, fifteenand eighteen-months-of-age in a series of behavioural tests covering specie-specific behaviour, motor activity and coordination, fear-, spatial and recognition memory as well as curiosity and emotionality. Whilst cognitively unimpaired, FKBP52+/- mice performed worse on an accelerating rotating rod than FKBP52+/+ littermates across all age-groups suggesting that FKBP52 is involved in processes controlling motor coordination. This deficit did not exacerbate with age but did worsen with repeated testing; pointing towards a role for FKBP52 in learning of tasks requiring motor coordination abilities. This study contributes to the knowledge base of FKBP52’s implication in neurodegenerative diseases by demonstrating that FKBP52 by itself does not directly affect cognition and may therefore rather play an indirect, modulatory role in the functional pathology of AD, whereas it directly affects motor coordination, an early sign of neurodegenerative damages to the brain.